The quest for ghost gear in the German Baltic Sea: A team effort between WWF, divers, fisherfolk, and public authorities - Andrea Stolte; Gabriele Dederer; Jochen Lamp; Crayton Fenn; Mareen Lee; Wolfgang Frank; Christian Howe; Michael Günther; Heike Vesper; Stefanie Werner (Frontiers in Marine Science, 2022)
In this pilot project, World Wild Fund for Nature (WWF) Germany works together with regional divers, fisherfolk and public authorities to reduce the impact of lost fishing gear in the Baltic Sea. If not removed, ghost gear poses a threat to the marine environment and wildlife including seabirds, seals, harbour porpoises and fish. Over decades to centuries, lost fishing nets and ropes shed microplastic fibres into the marine environment. Removing this hazard reduces both the risk of entanglement as well as the contamination of the marine foodweb through ingestion of microplastics and associated chemicals. Identifying lost fishing gear in the marine environment poses one of the largest challenges impeding mitigation through gear retrieval operations. Lost gear can be drifting on the surface, in the water column, or can be sunken to the seafloor as a result of material composition, fouling, and entanglement. In the Baltic Sea, ghost gear is located on the seafloor and not visible during visual surface surveys from vessels. Identifying an efficient search methodology was therefore a key aspect of WWF’s ghost gear project. After trials with different search and retrieval methodologies, WWF Germany found sonar search technology to be the most efficient technique to locate lost gear on the seafloor. Sound waves avoid the limitations faced by divers or visual cameras in low-visibility environments, and a substantially larger area can be covered. In contrast to diving teams focussing on wreck retrievals, the many nets lost on the seafloor remain unnoticed by divers under most circumstances. A combination of sonar search providing exact GPS positions of suspect ghost gear, diver verification through the WWF Ghostdiver App, point-on retrievals with fishing vessels, and manual sorting for waste management provides an efficient methodology for long-term political implementation of regular lost gear retrieval campaigns.